Parental income and the achievement of higher education in Sweden and Finland - Jäntti, Markus; Karonen, Esa (My University, 2026)
This study examines how parental income influences the likelihood that a child attains
higher education in Sweden and Finland. Recognizing that both parental income and
children's educational outcomes may be shaped by unobserved factors, we exploit
variation in local labour market conditions—particularly during the economic recessions of
the early 1990s—to identify the causal effects of childhood economic resources on later
educational attainment. Using high-quality register data covering the years 1987 to 2020,
we apply both instrumental variables and sibling fixed-effects approaches to address
endogeneity concerns and account for family-level unobserved heterogeneity. Our findings
suggest that parental economic resources play a significant role in shaping children's
educational outcomes. However, the strength of the association varies depending on the
measure of parental resources considered. Causal estimates derived from instrumental
variables tend to be larger than naive ordinary least squares estimates, indicating that
simple correlations may underestimate the true effects. Moreover, parental labour income
appears to be more consistently associated with children's educational attainment than
disposable household income, suggesting the importance of parental labour market
attachment beyond financial resources alone. Some evidence also points to maternal
income exerting a stronger influence than paternal income, although results differ by
country and specification. Overall, our results highlight the critical role of dynamic changes
in family economic conditions during childhood in shaping intergenerational educational
mobility